Designing a roadmap for human resource management in the Banking 4.0 - Iwa Kuchciak; Izabela Warwas (Journal of Risk and Financial Management, 2021)
The banking sector has been going through a rapid transformation due to digitalization, regulatory requirements, customer expectations, and demographic trends. The purpose of this paper is to provide an advanced overview of the practical applications of human resource management (HRM) in Banking 4.0. This study used quantitative and qualitative methods to present the results of good practice form inventory and a Delphi study. The results of a European study show that human resource management practices such as reskilling, upskilling, and redeployment are a solution to mitigate challenges in the Banking 4.0 era. The HRM roadmap for banks will be a major guide to ensure effective workforce management.
Keywords: 330; human resource management; HRM; Industry 4.0; Banking 4.0; digitalization